The Role of Phraseology and Formulaic Language in Facilitating Communication: A Corpus-Based Study - Abdulxapizova, Gulnoza; Tukhtxodjaeva, Zulfiya (The Lingua Spectrum, 2025)
This article investigates the significant role of phraseology and formulaic language in facilitating fluent and effective communication. Employing a corpus-based approach, the study examines the frequency, distribution, and functions of prefabricated language units, including idioms, collocations, and fixed expressions, in naturally occurring spoken and written discourse. The research analyzes how these formulaic sequences contribute to processing speed, reduce cognitive load for both speaker/writer and listener/reader, and enhance communicative clarity. Further analysis explores the relationship between phraseological competence and language proficiency, considering the implications for language learning and teaching. The study also addresses the potential impact of register, genre, and medium on the use and distribution of formulaic language. Ultimately, this research aims to provide empirical evidence for the crucial role of phraseology in streamlining communication and contributing to overall communicative success.